2006
DOI: 10.1111/j.1365-2249.2006.03134.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulins and complement factor C4 in adult rhinosinusitis

Abstract: SummaryWe assessed whether complement and its factor C4 or abnormal immunoglobulin levels are associated with chronic or recurrent rhinosinusitis. We used multiple patient and control groups to obtain clinically meaningful data. Adult chronic or recurrent rhinosinusitis and acute purulent rhinosinusitis patients were compared with unselected adults and controls without previous rhinosinusitis. Associated clinical factors were reviewed. Levels of immunoglobulins, plasma C3, C4 and classical pathway haemolytic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 49 publications
3
50
0
1
Order By: Relevance
“…[585][586][587][588][589] An association between hypoimmunoglobulinemia and CRS has been described in the literature and multiple studies have demonstrated PID as a risk factor for the development of CRS. 15,155,[590][591][592][593][594][595][596] The association is further strengthened by other studies that show an increased incidence of RS in patients with immune dysfunction. 586,587 CVID, X-linked hypogammaglobulinemia, and several other disorders of humoral immunity are frequently referenced as contributing factors to chronic or recurrent recalcitrant RS.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…[585][586][587][588][589] An association between hypoimmunoglobulinemia and CRS has been described in the literature and multiple studies have demonstrated PID as a risk factor for the development of CRS. 15,155,[590][591][592][593][594][595][596] The association is further strengthened by other studies that show an increased incidence of RS in patients with immune dysfunction. 586,587 CVID, X-linked hypogammaglobulinemia, and several other disorders of humoral immunity are frequently referenced as contributing factors to chronic or recurrent recalcitrant RS.…”
Section: Discussionsupporting
confidence: 62%
“…Two case-control studies have also examined this subject. Seppanen et al 591 compared CRS (including two thirds with CRSwNP) or RARS to ARS and controls. They demonstrated that low complement C4 levels were more associated with CRS or RARS than ARS and concluded that the isolated low IgG subclass alone had limited value in patient assessment.…”
Section: Viiic1h Crswnp Pathophysiologymentioning
confidence: 99%
See 2 more Smart Citations
“…47 In addition, C4 plays a defensive role against virus and encapsulated bacteria. 48,49 C4 deficiency may increase the infection chances such as acute otitis media, sinusitis, or pneumonia [49][50][51] which are the exacerbating factors for IgAN resulting in a poor prognosis. [52][53][54] Someone may presume that the low C4 levels here could be caused by the activation of complement cascade.…”
Section: Discussionmentioning
confidence: 99%